Multimodal Interaction between a Mother and Her Twin Preterm Infants (Male and Female) in Maternal Speech and Humming during Kangaroo Care: A Microanalytical Case Study - Eduarda Carvalho; Raul Rincon; João Justo; Helena Rodrigues (MDPI AG, 2021)
The literature reports the benefits of multimodal interaction with the maternal voice for preterm dyads in kangaroo care. Little is known about multimodal interaction and vocal modulation between preterm mother-twin dyads. This study aims to deepen the knowledge about multimodal interaction (maternal touch, mother's and infants' vocalizations and infants' gaze) between a mother and her twin preterm infants (twin 1 [female] and twin 2 [male]) during speech and humming in kangaroo care. A microanalytical case study was carried out using ELAN, PRAAT, and MAXQDA software (Version R20.4.0). Descriptive and comparative analysis was performed using SPSS software (Version V27). We observed: (1) significantly longer humming phrases to twin 2 than to twin 1 (p = 0.002), (2) significantly longer instances of maternal touch in humming than in speech to twin 1 (p = 0.000), (3) a significant increase in the pitch of maternal speech after twin 2 gazed (p = 0.002), and (4) a significant increase of pitch in humming after twin 1 vocalized (p = 0.026). This exploratory study contributes to questioning the role of maternal touch during humming in kangaroo care, as well as the mediating role of the infant's gender and visual and vocal behavior in the tonal change of humming or speech.